Growth and survival of Collosoma sp. larvae at different water exchange rate in recirculating aquaculture system - Sabariah, . (Jurnal Akuakultur Indonesia, 2010)
Recirculating aquaculture system (RAS) is one of aquaculture systems that aimed at providing good water quality as fish culture medium. The objective of this study was to examine the effect of water exchange rate in RAS on the growth and survival of Collosoma sp. Four different water exchange rates were tested, i.e. 0.003 ℓ/s, 0.005 ℓ/s, 0.008 ℓ/s, and 0.010 ℓ/s. Collosoma sp. larvae was stocked at a density of 50 fish/ℓ in plastic jar with a volume of 4ℓ. The observation showed that water exchange rate of 0.005 ℓ/s resulted in the best survival and growth. Key words: Circulating system, Collosoma larvae, water exchange rate, growth, survival ABSTRAK Akuakultur sistem sirkulasi merupakan salah satu sistem budidaya yang bertujuan untuk menyediakan kualitas air yang baik sebagai media pemeliharaan ikan. Tujuan penelitian ini adalah untuk mempelajari pengaruh laju pergantian air terhadap kelangsungan hidup dan pertumbuhan larva ikan bawal Collosoma sp. Perlakuan meliputi empat laju pergantian air yang berbeda yaitu, 0,003 ℓ/detik; 0,005 ℓ/detik; 0,008 ℓ/detik; and 0,010 ℓ/detik. Larva ikan bawal kemudian ditebar dalam stoples plastic dengan volume 4ℓ dengan kepadatan 50 ekor/ℓ. Hasil penelitian menunjukkan bahwa laju pergantian air sebanyak 0,005 ℓ/detik memberikan kelangsungan hidup dan pertumbuhan ikan bawal terbaik. Kata-kata kunci: Sirkulasi, larva ikan bawal, laju pergantian air, pertumbuhan, kelangsungan hidup